Altered structural covariance of the striatum in functional dyspepsia patients. Issue 8 (28th May 2014) - Liu, P.; Zeng, F.; Yang, F.; Wang, J.; Liu, X.; Wang, Q.; Zhou, G.; Zhang, D.; Zhu, M.; Zhao, R.; Wang, A.; Gong, Q.; et al.
Abstract Background Functional dyspepsia (FD) is thought to be involved in dysregulation within the brain–gut axis. Recently, altered striatum activation has been reported in patients with FD. However, the gray matter (GM) volumes in the striatum and structural covariance patterns of this area are rarely explored. The purpose of this study was to examine the GM volumes and structural covariance patterns of the striatum between FD patients and healthy controls (HCs). Methods T1‐weighted magnetic resonance images were obtained from 44 FD patients and 39 HCs. Voxel‐based morphometry (VBM) analysis was adopted to examine the GM volumes in the two groups. The caudate‐ or putamen‐related regions identified from VBM analysis were then used as seeds to map the whole brain voxel‐wise structural covariance patterns. Finally, a correlation analysis was used to investigate the effects of FD symptoms on the striatum. Key Results The results showed increased GM volumes in the bilateral putamen and right caudate. Compared with the structural covariance patterns of the HCs, the FD‐related differences were mainly located in the amygdala, hippocampus/parahippocampus (HIPP/paraHIPP), thalamus, lingual gyrus, and cerebellum. And significant positive correlations were found between the volumes in the striatum and the FD duration in the patients. Conclusions & Inferences These findings provided preliminary evidence for GM changes in the striatum and different structural covariance patterns in patients with FD. The current results might expand our understanding of the pathophysiology of FD.